PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nadaredo, Salsa Haliza; Kinasih, Hayu Wikan; Pratiwi, Ririh Dian; Prajanto, Agung; Fuad, Khoirul (Universitas Dian Nuswantoro, 2025)
This study aims to determine how profitability, liquidity, capital structure, dividend policy, and company size affect company value as determined by the price-to-book value (PBV) ratio. Sampling with purposive sampling technique is used together with quantitative methods to collect data. By using 58 company data in the energy industry listed between 2021 and 2023 on the Indonesia Stock Exchange. The analysis tool used is multiple linear regression through the SPSS program. The findings in this study reveal that the variables profitability, dividend policy, capital structure, and company size affect company value. In addition, this study produces a liquidity variable that does not affect company value. The implication of this study is the importance of companies paying attention to financial performance and company policies to increase company value.